2018
DOI: 10.1134/s1063773718070010
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Mira–Type Star T UMi

Abstract: Stellar evolution calculations were carried out from the main sequence to the final stage of the asymptotic giant branch for stars with initial masses 1M ⊙ ≤ M ZAMS ≤ 2M ⊙ and metallicity Z = 0.01. Selected models of evolutionary sequences were used as initial conditions for solution of the equations of radiation hydrodynamics and time-dependent convection describing radial stellar pulsations. The study was aimed to construct the hydrodynamic models of Mira-type stars that show the secular decrease in the puls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…As Templeton et al (2005) pointed out, models in the 1990s usually used time steps in the order of centuries-far too sparse for a quantitative comparison with the changes seen in T UMi. The only attempt so far to model T UMi both in terms of evolution and pulsation was done very recently by Fadeyev (2018). He found that a 1.2 M initial-mass model fit the observations best, transitioning from a fundamental-mode pulsation around 315 d to first-overtone pulsation near 114 d. He also derived physical parameters, obtaining a luminosity of 4080 L , a radius of 220 R , and an age of 4.3 × 10 9 yr.…”
Section: T Ursae Minorismentioning
confidence: 99%
See 1 more Smart Citation
“…As Templeton et al (2005) pointed out, models in the 1990s usually used time steps in the order of centuries-far too sparse for a quantitative comparison with the changes seen in T UMi. The only attempt so far to model T UMi both in terms of evolution and pulsation was done very recently by Fadeyev (2018). He found that a 1.2 M initial-mass model fit the observations best, transitioning from a fundamental-mode pulsation around 315 d to first-overtone pulsation near 114 d. He also derived physical parameters, obtaining a luminosity of 4080 L , a radius of 220 R , and an age of 4.3 × 10 9 yr.…”
Section: T Ursae Minorismentioning
confidence: 99%
“…While this range is very broad, the lower limit rules out stars above 3 M . The upper limit corresponds to masses around 1.2-1.3 M , meaning that the 1.2 M model preferred by Fadeyev (2018) is already bordering this constraint. Feast & Whitelock (2000) collected average [Fe/H] indices of globular clusters with Miras and semiregular variables in them.…”
Section: Age and [Fe/h]mentioning
confidence: 99%
“…The photometric variability due to stellar pulsations is a typical property of post-AGB stars. The period of light variations ranges from several dozen days (Arkhipova et al, 2010;Hrivnak et al2015;2018) to Π ≈ 200 day (Arkhipova et al, 2009;Ikonnikova et al, 2018). Moreover, the pulsating variable AI CMi with period Π ≈ 310 day seems to be the early post-AGB star (Arkhipova et al, 2017).…”
Section: Introductionmentioning
confidence: 94%
“…As in our earlier studies devoted to nonlinear pulsations of AGB stars (Fadeyev, 2017;2018) the pulsation period Π was determined using the discrete Fourier transform of the kinetic energy of the pulsating stellar envelope. Thus, the period estimate of each hydrodynamic model was obtained by averaging over the time interval of the solution of the equations of hydrodynamics.…”
Section: Hydrodynamic Models Of Post-agb Starsmentioning
confidence: 99%
See 1 more Smart Citation